Analisis Manajemen Resiko Keamanan Informasi pada Kantor Dinas Pendidikan Gunung Tua - Lili Saputri; Mirna Annifah Hsb; Tursina Juliani (Departement of Mathematics Education, 2023)
Implementation of Information Technology in government institutions is currently needed to facilitate data collection and strategic decision making. The Tax Service Office is one of the government agencies engaged in education. The Education Officeiis ia government agency located in theiGunung Tua Regency Government iOfficeiComplex, in its services such as processing data fromieach school, which isiiniPesawaran Regency whichican be used in processing certification data. Information technology analysis is carried out to ensure the operational continuity used byithe service, whether the existing information technology is used as well as ipossible, because if itiis not iused properly it will cause isome problems or existing losses suchias data loss, or ierrors. idata iuse, computer abuse, inaccurate information, because in this system the data is confidential and isensitive. iFor this reason, an Information Security Management System (ISMS) isineeded in managing its isecurity. iIn implementing ISO 27001ipreviously required information security risk imanagement. iThis risk management iactivity iis ineeded ito determine ithe iControl iObjectives ithat iwill ibe itaken ito handle irisks ithat imight ioccur. iIn implementing risk management, results were obtained only for username and password ilevel iassets ithat ihadiaihigh irisk i(6.67%) iof the 15 assets ithat ihad been iregistered, so that isecurity icontrols irelated ito iusernames iand ipasswords iwere ineeded ito minimize ior ireduce irisk.